Implementation of House of Risk (Hor) Model for Mitigating Raw Material Supply Chain Risk at PT. Raja Indonesia Perkasa - slamet (Journal Knowledge Industrial Engineering (JKIE), 2023)
Supply chain activities always carry the potential for risk, which is why risk management is essential for addressing these risks. In companies that manufacture mattresses, such as PT Raja Indonesia Perkasa Suwayuwo, the supply chain activities related to leather raw materials are susceptible to various risks. Therefore, it is necessary to conduct a risk analysis and design mitigation actions to address or reduce the likelihood of risks or disruptions in the leather raw material supply chain. This study employs the House of Risk (HoR) model, which consists of two phases. The first phase involves identifying risks and risk agents, followed by measuring the severity and occurrence levels, as well as calculating the Aggregate Risk Priority (ARP) values. The second phase focuses on risk treatment. The results of the study show that there are 27 risk events and 52 risk agents identified. Furthermore, six mitigation actions have been proposed, which are expected to effectively mitigate the risks in the leather raw material supply chain.